Novel sources of drought tolerance from landraces and wild sorghum relatives. Issue 1 (5th November 2020) - Ochieng, Grace; Ngugi, Kahiu; Wamalwa, Lydia N.; Manyasa, Eric; Muchira, Nicoleta; Nyamongo, Desterio; Odeny, Damaris A.
Abstract: Sorghum ( Sorghum bicolor [L.] Moench) is the fifth most important cereal crop worldwide and second after maize ( Zea mays L.) in Kenya. It is an important food security crop in arid and semi‐arid lands, where its production potential is hampered by drought. Drought tolerance can be measured by a plant's ability to resist premature senescence, often described as stay‐green. This study was carried out with the objective of identifying novel stay‐green trait among wild and landrace genotypes of sorghum. Forty‐four sorghum genotypes that included 16 improved, nine landraces, and 17 wild relatives of sorghum alongside known stay‐green sources, B35 and E36‐1, were evaluated under well‐watered and water‐stressed conditions in an alpha‐lattice design of three replications. Data was collected on plant height (PHT), flag leaf area (FLA), panicle weight (PWT), 100‐seed weight (HSW), relative chlorophyll content (RCC), number of green leaves at maturity (GLAM), days to 50% flowering (DFL), and grain yield (YLD). Genetic diversity was determined using diversity arrays technology (DArT) sequencing and quality control (QC) markers were generated using a java script. Lodoka, a landrace, was the most drought‐tolerant genotype, recorded the highest numbers of RCC and GLAM, and outperformed B35 and E36‐1 in yield under water‐stress and well‐watered conditions. The RCC was highly correlated with GLAM ( r = .71) and with yield‐related traits, HSW ( r = .85), PWT ( r = .82), and YLD ( r = .78). All traits revealed high heritability (broad‐sense) ranging from 60.14 to 98.4% for RCC and DFL, respectively. These results confirm earlier reports that wild relatives and landraces are a good source of drought tolerance alleles.